Analysis of the inner rainbands of tropical cyclones over the South China Sea during the landfall process - Xiang, Chunyi; Xu, Yinglong; Lin, Jian; Liu, Shuang (Frontiers in Earth Science, 2022)
Tropical Cyclones (TCs) can undergo offshore Rapid Intensification (RI) shortly before making landfall over the South China Sea (SCS). In this study, the inner rainbands distribution of both RI and non-RI Landfall TCs (LTCs) in the SCS during 2015-2020 is examined based on multi-source merged precipitation dataset. It is found that those RI LTCs exhibit a relatively higher averaged rain rate in the inner core region than that of non-RI LTCs. Both offshore RI cases and non-RI LTCs appear an increasing tendency of averaged rain rate after landfall, with the rain rate peak of the RI cases a few hours earlier than that of non-RI cases. By defining an axisymmetric index, the inner rainbands evolution of both offshore RI cases and non-RI ones are further discussed. For both two categories, most of axisymmetric rainfall is concentric around the center with over 70% axisymmetric rainfall dominates the inner core region within 3 times of Radius of Maximum Wind speed (RMW). It is shown that there is an obvious inwards shrinkage of axisymmetric rainfall for both offshore RI and non-RI cases. Analysis of typical RI and non-RI LTCs (1713 Hato and 1714 Pakhar) can also show an increasing rain rate of the inner rainbands soon after its landfall, with larger amplitude for RI example than non-RI case. The inner rainbands of 1713 Hato shown up a clockwise propagation with maximum enhancement happened at down-shear left side within few hours after landfall.